Control of the East‐West Component of the Interplanetary Magnetic Field on the Occurrence of Magnetic Substorms. Issue 5 (10th March 2020) - Liou, Kan; Sotirelis, Thomas; Mitchell, Elizabeth
Abstract: We study the effects of the east‐west ( y ) component of the interplanetary magnetic field (IMF) on the occurrence of substorms by analyzing 16, 743 magnetic substorm events identified with the SuperMAG SML index from 1995 to 2016. It is found, surprisingly, that substorm occurrence rates depend highly on the sign of IMF B y, with, on average, 1/3 more substorms for IMF B y > 0 than for IMF B y < 0. We attribute this asymmetry to the enhanced convection (e.g., more energy in the tail) under IMF B y > 0 conditions. A superposed epoch analysis of the IMF indicates that the average IMF B y prior to onset is positive but becomes less positive 15 min prior to the onset, indicating that the release of the stress associated with a clockwise twisted magnetotail may be an important onset trigger. We conjecture that an asymmetry in the dayside merging efficiency may be the cause. Key Points: Substorms are more (less) frequent under positive (negative) IMF B y conditions The majority of substorm events occur 15 min after a reduction of the IMF B y component